Remineralização de lesões de mancha branca adjacentes aos bráquetes ortodônticos - Restrepo, Manuel Restrepo [UNESP] (2013)
The aim of this study was to evaluate and quantify the remineralization process on white spot enamel lesions adjacent to orthodontic braces. In the in vitro study, orthodontic braces were bonded in 30 extracted premolars that remained in a special solution for artificial enamel lesion development. Teeth were divided into three gropus (n=10), control (CO), varnish fluoride (VF) and chlorehexidine gel 2% (CHX). The demineralization process was assessed by Quantitative Light-Induced Fluorescence (QLF). In the vivo study, 30 healthy adolescents (mean age ± standard deviation: 17.2 ± 2.3 years) (n=56 lesions) undergoing orthodontic treatment with fixed appliances were enrolled in a double blind, randomized, longitudinal trial lasting three months. The subjects were randomly divided into three groups, using varnish fluoride (n=20), chlorexidine gel 2% (n=17) or fluoride toothpaste (n=19). The remineralization process was evaluated and quantified by Nyvad criteria (NY) and DIAGNOdent pen (DDpen). In both studies, the products were applied twice with one-week interval. All groups in the in vitro study, showed an increase in fluorescence (Delta F, %), whereas lesions treated with varnish fluoride had a quicker and more favorable response to remineralization. In the vivo study, fluorescence decreased during the experimental period, and lesions in the VF group had a quicker and more favorable response to remineralization. The correlation between DDpen and NY was 0.67 (Sperman, p<0.05). Two applications of varnish fluoride supplementated with oral hygiene and fluoride tooth paste, are effective in reversing WSLs during orthodontic treatment.